The Impact Of Digital Service Quality And Consumer Trust On Customer Loyalty With Customer Satisfaction As A Mediator (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This research investigates the intricate relationships among digital service quality, consumer trust, customer satisfaction, and customer loyalty within the context of PDAM Trenggalek, a municipal water utility service. Utilizing a sample of 65 individuals through a Random Sampling technique, the study employs Structural Equation Modeling (SEM) with Partial Least Squares (PLS) analysis using Smart PLS software. The results reveal a significant direct impact of digital service quality on consumer trust and customer loyalty, emphasizing the crucial role of seamless digital services in cultivating customer satisfaction and loyalty. Furthermore, a significant relationship is identified between consumer trust and customer loyalty, highlighting the importance of consumer trust in fostering customer loyalty. However, the indirect relationship between consumer trust and customer loyalty, mediated by customer satisfaction, is found to be not statistically significant in the examined sample. The findings underscore the strategic importance of prioritizing digital service quality and building consumer trust to enhance customer satisfaction and foster lasting loyalty in the competitive landscape of municipal water utility services. This research contributes valuable insights that can inform strategic initiatives for PDAM Trenggalek to optimize customer experiences and strengthen customer relationships.
Keywords: Digital Service Quality, Consumer Trust, Customer Satisfaction, Customer Loyalty, Municipal Water Utility